Diagnostic value of the MZXBTCH scoring system for acute complex appendicitis - Tianyi Ma; Qian Zhang; Hongwei Zhao; Peng Zhang (Scientific Reports)
Abstract The objective of this study was to develop a novel scoring model, assess its diagnostic value for complex appendicitis, and compare it with existing scoring systems. A total of 1,241 patients with acute appendicitis were included, comprising 868 patients in the modeling group (mean age, 35.6 ± 14.2 years; 52.4% men) and 373 patients in the validation group (mean age, 36.2 ± 13.8 years; 53.1% men). Among them, 28.4% (346/1,241) were diagnosed with complex appendicitis. The distribution of clinical features, laboratory results, and imaging findings was comparable between the two groups. The data from the modeling group were used to develop the MZXBTCH scoring system, which subsequently validated using the validation group data. Based on postoperative pathological diagnoses, the validation group (n = 373) was scored using the Alvarado, Raja Isteri Pengiran Anak Saleha (RIPASA), Appendicitis Inflammatory Response (AIR), and MZXBTCH scoring systems. Receiver operating characteristic (ROC) curves were plotted to compare the diagnostic efficacy of these scoring systems for complex appendicitis. Multivariate logistic regression analysis identified preoperative body temperature (odds ratio (OR) = 1.104; 95% confidence interval (CI) 1.067–1.143; P < 0.001), preoperative C-reactive protein (CRP) level (OR = 1.002; 95% CI 1.001–1.002; P < 0.001), lymphocyte percentage (OR = 0.994; 95% CI 0.990–0.996; P < 0.001), appendiceal fecal stones (OR = 1.127; 95% CI 1.068–1.190; P < 0.001), periappendiceal fat stranding (OR = 1.133; 95% CI 1.072–1.198; P < 0.001), and appendix diameter (OR = 1.013; 95% CI 1.004–1.022; P < 0.001) as independent risk factors for complex appendicitis. Using R programming, a nomogram based on these independent risk factors was constructed to derive MZXBTCH scores. ROC curve analysis of the MZXBTCH model indicated an area under the curve (AUC) of 0.773. ROC curve analysis revealed that the AUC values of the Alvarado, RIPASA, AIR, and MZXBTCH scoring systems were 0.66, 0.68, 0.76, and 0.82, respectively. Sensitivities were 64.29%, 66.33%, 68.37%, and 74.49%, and specificities were 55.64%, 60%, 75.64%, and 76.36%, respectively. Positive predictive values were 0.34, 0.37, 0.5, and 0.53, while negative predictive values were 0.81, 0.83, 0.87, and 0.89. Accuracy rates were 0.58, 0.62, 0.74, and 0.76, respectively. The MZXBTCH scoring system demonstrated higher sensitivity, specificity, and accuracy compared with the Alvarado, RIPASA, and AIR scoring systems in distinguishing complex appendicitis.